Mechanical Performance of Fly-Ash-Based Green Geopolymer Composites Subjected to Elevated Temperatures - Choi, Y.C.; Kim, J.H.; Choi, S. (Asian Journal of Chemistry, 2014)
This paper discusses the effect of Na2O content, SiO2/Na2O mole ratio and elevated temperature on the mechanical performance of fly-ash-based inorganic green geopolymer composites. Fly-ash-based geopolymers, which were manufactured with varying alkali contents (4-8 % of fly ash weight) and SiO2/Na2O mole ratios (0.6-1.4), were subjected to elevated temperatures up to 900 ºC. The geopolymer composites and their performance were evaluated on the basis of weight loss and strength loss after temperature exposure. In addition, mineralogical changes due to the elevated temperature exposure were studied using X-ray diffraction. Investigation of microstructures as well as microprobe analysis was performed using scanning electron microscopy, Fourier-transform infrared spectroscopy and mercury intrusion porosimetry. The results showed that the fly-ash-based geopolymer responded significantly to high temperature conditions.